2022
DOI: 10.1186/s12879-022-07336-z
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and associated risk factors of soil-transmitted helminth infections in Kandahar, Afghanistan

Abstract: Background Soil-transmitted helminth (STH) infections are still a major health problem, especially in resource-limited countries. The community-based prevalence of STH is unknown in Afghanistan. Main objectives of this study were to estimate the prevalence and associated factors of STH among children in Daman district of Kandahar province in Afghanistan. Methods This was a community-based cross-sectional study, with data collected during five month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In 2020, a community-based study in rural children of Daman district in Kandahar Afghanistan also reported A . lumbricoides as the most prevalent STH species (18.7%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, a community-based study in rural children of Daman district in Kandahar Afghanistan also reported A . lumbricoides as the most prevalent STH species (18.7%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall prevalence of STH infection was 22.7%. Main risk factors associated with the predisposition of rural children for getting STH were not washing hands after defecating/before eating, living in mud house, walking barefoot, living in overcrowded house, and practicing open defecation [ 21 ]. In another hospital-based study in Afghanistan, 548 fecal samples were collected from the patients (both children and adults) with internal complaints who were admitted in two hospitals of Ghazni and Parwan provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Those findings are also consistent with the findings of previous studies. 37 , 38 , 39 , 40 Hookworm is the dominant species of soil-transmitted helminths, and barefoot labor is a known risk factor for hookworm infection. Therefore, changing the culture of barefoot labor is an important strategy for soil-transmitted helminth control.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was identified in the Funding section.…”
Section: Correction To: Bmc Infectious Diseases (2022) 22:361 101186/...mentioning
confidence: 99%